Pendampingan Bazar di Pasar Talang Padang untuk Meningkatkan Pendapatan UMKM di Talang Padang Kabupaten Tanggamus - Muhammad Mufti Hudani; Resha Moniyana Putri; Arivina Ratih Yulihar Taher; Rizka Malia; Mega Mariska; Nindya Eka Sobita; Vitriyani Tri Purwaningsih (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
Modern markets have an impact on changes in profit levels in traditional markets in an area, although they do not have an impact on changes in turnover and the number of people working in traditional markets. The Service Team took the initiative to create a bazaar activity for MSMEs in Talang Padang, Tanggamus Regency with a strategy of providing free bazaar stands for 7 bazaar days. It is hoped that this activity can revive the market which was sluggish after the renovation and can provide space for micro, small and medium businesses to promote their superior products directly to the public.